Dissent! Refracted : Histories, Aesthetics and Cultures of Dissent - Dorfman, Benjamin (2016)
This collection of essays addresses the ongoing problem of dissent from a broad range of disciplinary perspectives: political philosophy, intellectual history, literary studies, aesthetics, architectural history and conceptualizations of the political past. Taking a global perspective, the volume examines the history of dissent both inside and outside the West, through events in the twentieth and twenty-first centuries both nearer to our own times as well as more distant, and through a range of styles reflecting how contested and pressing the problem of dissent in fact is. Drawing on a range of authors and international problematics, the contributions discuss the multiple ways in which we refract memories of dissent in cultural, historical and aesthetic context. It also discusses the diverse ideas, images and phenomena we use to do so.